ABCG1 influences the brain cholesterol biosynthetic pathway but does not affect amyloid precursor protein or apolipoprotein E metabolism in vivo - Burgess, Braydon L.; Parkinson, Pamela F.; Racke, Margaret M.; Hirsch-Reinshagen, Veronica; Fan, Jianjia; Wong, Charmaine; Stukas, Sophie; Theroux, Louise; Chan, Jeniffer Y.; Donkin, James; Wilkinson, Anna; Balik, Danielle; et al. (Journal of lipid research, 2008)
Cholesterol homeostasis is of emerging therapeutic importance for Alzheimer's disease (AD). Agonists of liver-X-receptors (LXRs) stimulate several genes that regulate cholesterol homeostasis, and synthetic LXR agonists decrease neuropathological and cognitive phenotypes in AD mouse models. The cholesterol transporter ABCG1 is LXR-responsive and highly expressed in brain. In vitro, conflicting reports exist as to whether ABCG1 promotes or impedes Aβ production. To clarify the in vivo roles of ABCG1 in Aβ metabolism and brain cholesterol homeostasis, we assessed neuropathological and cognitive outcome measures in PDAPP mice expressing excess transgenic ABCG1. A 6-fold increase in ABCG1 levels did not alter Aβ, amyloid, apolipoprotein E levels, cholesterol efflux, or cognitive performance in PDAPP mice. Furthermore, endogenous murine Aβ levels were unchanged in both ABCG1-overexpressing or ABCG1-deficient mice. These data argue against a direct role for ABCG1 in AD. However, excess ABCG1 is associated with decreased levels of sterol precursors and increased levels of SREBP-2 and HMG-CoA-reductase mRNA, whereas deficiency of ABCG1 leads to the opposite effects. Although functions for ABCG1 in cholesterol efflux and Aβ metabolism have been proposed based on results with cellular model systems, the in vivo role of this enigmatic transporter may be largely one of regulating the sterol biosynthetic pathway.